Epidermal growth factor receptor, p16, cyclin D1, and p53 staining patterns for inverted papilloma. Issue 11 (26th August 2013) - Lin, Giant C.; Scheel, Adam; Akkina, Sarah; Chinn, Steven; Graham, Martin; Komarck, Christine; Walline, Heather; McHugh, Jonathan B.; Prince, Mark E.; Carey, Thomas E; Zacharek, Mark A.
<x xml:space="preserve">Abstract</x> Background The aim of this study was better characterize the staining patterns of inverted papilloma (IP) with and without carcinoma by performing immunohistochemistry for p16, epidermal growth factor receptor (EGFR), p53, and cyclin D1 antibodies in a large patient cohort. Methods A total of 162 IP specimens were collected from 147 patients treated at the University of Michigan between 1996 and 2011. Twenty‐two specimens contained carcinoma. Tumor was extracted for construction of 2 tissue microarrays and stained for p16, EGFR, p53, and cyclin D1. Tumor staining intensity and percentage staining were scored. Results Benign disease was positive for p16 in 64%, EGFR in 50%, p53 in 30%, and cyclin D1 in 76%. IP with carcinomatous degeneration was positive for p16 in 14%, EGFR in 71%, p53 in 62%, and cyclin D1 in 76%. The differences in staining positivity between benign and malignant disease reached significance for p16 and p53 only. Mean percentage staining by tumor surface area for IP and IP with carcinoma was 12% vs 7% for p16 (no statistical significance [NS]), 20% vs 34% for EGFR (NS), 4% vs 24% for p53 (p < 0.001), and 17% vs 21% for cyclin D1 (NS). Conclusion Important characteristic staining pattern for IP with and without carcinoma are highlighted in this study. Unlike recent trends in human papilloma virus (HPV)‐related head and neck malignancies, low expression of p16 is a marker for malignancy in this series. Positive staining for p53 correlates with the development of carcinoma in IP.